Neosporosis bovina: una parasitosis que amenaza la productividad de la ganadería altoandina - Pineda Serruto, Martin Equicio (2025)
In order to describe bovine neosporosis as a livestock health problem in the Andes, the determinants, epidemiology and control of this parasitosis were identified, for this purpose a review of the literature published in the ScienceDirect collection was made, finding that the canine is the main determinant for bovine neosporosis, as a propagator in the stable of the protozoan Neospora caninum, other factors are related to the components of the production system and cattle breeds; It was observed that horizontal transmission of bovine neosporosis occurs through dog excreta contaminating cattle feed and vertical transmission occurs in young cows with low immunity, thus affecting their offspring, with fetuses being infected by N. caninum, causing abortions or reproductive problems such as return to estrus or temporary loss of estrus, a situation that causes important economic losses for cattle breeders. Through serological and molecular laboratory analysis, positive cases of N. caninum were diagnosed in the population, estimating seroprevalences of bovine neosporosis in different geographical areas of the world, with rural areas being more affected. The magnitude of the epidemiological association between neosporosis and its determinants was also measured by estimating odds ratios (OR), prevalence ratios (PR) and hazard ratios (HR), this information is useful for the development of control strategies based on specific biosecurity actions; meanwhile, effective treatments and vaccines are being developed.